2019
DOI: 10.1186/s12957-019-1655-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors for anastomotic leakage after anterior resection of rectal cancer in elderly patients over 80 years old: an analysis of 288 consecutive patients

Abstract: Background Anastomotic leakage (AL) is a common complication after anterior resection of rectal cancer. Few studies have been conducted to determine whether the traditional predictors of AL can be applied to elderly patients (age ≥ 80) undergoing anterior resection (AR) or low anterior resection (LAR) of rectal cancer. This study was designed to explore the predictive factors for AL after anterior resection of rectal cancer in patients over 80 years old. Methods From Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…In the present study, a total of 21 (10.1%) patients developed AL after laparoscopic resection with transrectal NOSE for rectal cancer and sigmoid colon cancer, and the incidence of AL was basically consistent with that of traditional laparoscopic surgery. [4][5][6][7][8][9] In recent years, several risk factors associated with AL have been reported in a large number of studies, 4,5,8,13 but few studies have examined the potential risk factors for AL after laparoscopic resection with transrectal NOSE for colorectal cancer. The univariate and multivariate analyses in this study uncovered that a duration of operation ≥140 min (OR = 5427, 95% CI = 1.355-21.727, P = .017) was an independent predictive factor for AL after transrectal NOSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a total of 21 (10.1%) patients developed AL after laparoscopic resection with transrectal NOSE for rectal cancer and sigmoid colon cancer, and the incidence of AL was basically consistent with that of traditional laparoscopic surgery. [4][5][6][7][8][9] In recent years, several risk factors associated with AL have been reported in a large number of studies, 4,5,8,13 but few studies have examined the potential risk factors for AL after laparoscopic resection with transrectal NOSE for colorectal cancer. The univariate and multivariate analyses in this study uncovered that a duration of operation ≥140 min (OR = 5427, 95% CI = 1.355-21.727, P = .017) was an independent predictive factor for AL after transrectal NOSE.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Anastomotic leakage (AL) remains the most feared surgical complication following anterior resection for colorectal cancer, with an incidence rate of 7.5-10.4%. [4][5][6][7][8][9] The occurrence of AL not only has negative effects on quality of life and long-term prognosis but also delays the length of hospitalization and wastes unnecessary medical resources. [8][9][10][11][12] Previous studies have demonstrated that sex, 8 coronary heart disease, 4,13 the type of surgical method, 5 the preoperative albumin level, 13 and other factors are predictive factors for AL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated a rate of AL of 4%-29 %, [11][12][13][14] and several risk factors for AL after colorectal cancer surgery have been discussed [20][21][22], as well as methods to reduce the rate, prevent AL, and the related risk factors [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…2,10 This estimate includes asymptomatic AL with an incidence as high as 50%. 11 In case of AL, the duration of hospitalization is doubled and perioperative mortality is tripled compared to the normal healing process of CA. 2 Many factors affect the healing of CA.…”
Section: Introductionmentioning
confidence: 99%